Superiority of pan-immune inflammation value, systemic inflammation index, and CALLY scores prognostic value for mortality of ischemic stroke patients followed in intensive care unit - Altuntas, Gulsum; Yildirim, Rahmet; Demirel, Ismail (Bmc, 2025)
Aims The Inflammatory response plays an important role in the pathophysiology and prognosis of ischemic stroke. Hyperinflammation progresses with aggravation of brain damage and deterioration in clinical status. The study aimed to demonstrate a valuable, easy-to-obtain, and inexpensive parameter for prognostic assessment by comparing the Pan-immune Inflammation Value (PIV), Systemic Immune-Inflammation Index (SII), and CALLY scores in patients with ischemic stroke. Methods In this retrospective single-center cohort study, the files of patients who were followed up with a diagnosis of ischemic stroke in the tertiary intensive care units. Multivariate regression analysis and receiver operating characteristic curves(ROC) were used to detect the association between PIV, SII, and CALLY on in-hospital mortality and their superiority over each other in predicting mortality in ischemic stroke patients. Results Of 1,039 patients, 453 died, resulting in an overall survival rate of 56.4%. In the multivariate analysis, high APACHE II scores and low albumin levels remained independent risk factors. ROC curves showed that PIV, SII, and CALLY exhibited good predictive values, with AUCs of 0.921, 0.887, and 0.930 (95% CI: 0.903-0.936, 0.855-0.896, 0.913-0.945; p < 0.001). A pairwise comparison of the data based on AUC values indicated a significant difference between SII and both PIV and CALLY (p < 0.001). In contrast, no significant difference was found between PIV and CALLY (p = 0.385). Conclusion The PIV, SII, and CALLY indices serve as accessible and reliable prognostic biomarkers that can enhance personalized treatment strategies and improve clinical decision-making in patients with ischemic stroke.
Keywords: Pan-immune-inflammation value; Ischemic stroke; Systemic immune inflammation; Inflammation biomarker; CALLY index